PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN (SAP) BERBASIS AKRUAL DAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN GUNUNG KIDUL - Kurnia Rahmah; Zulkifli Zulkifli (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2018)
This research aims to analyze the effect of application of government accounting standard and the effect of region’s financial accounting system on the quality of regency financial statements GunungKidul regency (empirical study at government institutions in GunungKidul regency DIY). There are 36 respondents in this research uses purposive sampling method. SPSS 17.0 is used to analyze hypotheses in this research. Based on the result of this research are application of accrual basis government accounting standard influence positively, but not significant on quality of regency financial statements GunungKidul regency, and region’s financial accounting system influence positively, but not significant on quality of regency financial statements Gunung Kidul regency.